Development of Best Beta CAPM with Adjustment of Sharia Elements: A Case Study on Sharia Stocks in Indonesia - Aziz, Abdul; ., Supriyanto; ., Abdurakhman (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
This paper introduces the Best Sharia-based Capital Asset Pricing Model (BSCAPM), a modification of the BCAPM model integrating Islamic finance principles. This study focuses on optimizing the beta parameter within the model by integrating Sharia-compliant factors such as zakat and purification, while excluding short-selling practices. Using data from the Jakarta Islamic Index (JII) from June 2020 to November 2024, the BSCAPM portfolio outperforms the BCAPM portfolio in terms of the Sharpe ratio. The findings indicate that the BSCAPM serves as a viable alternative framework for Islamic investment modelling, providing Muslim investors with a Sharia-compliant, optimal portfolio formation model. The research contributes to the underexplored domain of portfolio selection modelling in the Islamic sector, enriching references on asset pricing in Sharia portfolios, particularly in the Indonesian Sharia stock market.